Implementasi Strategi Pemasaran Produk Melalui Packaging dan Kebersihan Produk untuk Menjamin Keberlangsungan Usaha Masyarakat Denai Lama Kecamatan Pantai Labu Kabupaten Deli Serdang - Tety Novriyanti Zebua; Elva Citra Sari; Ikmal Husein Lubis; Siti Humaira; Johan Manurung; Lamriama Valintina Chrystina Siregar; Yeni Absah (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2024)
To ensure the competitiveness and sustainability of community businesses, one strategy that needs to be implemented is to focus on packaging (product packaging) and product cleanliness. Denai Lama Village, located in Pantai Labu District, Deli Serdang Regency, is one of the tourist villages that has a traditional market that produces local products, especially in the food and handicraft sectors, so that it has its own appeal and can be a significant source of income for the local community. The main objective of this community service is to implement product marketing strategies through product packaging and cleanliness in order to support the desires of the community. In addition to conducting socialization to Traditional Market traders in the Denai Lama tourist village, namely Paloh Naga Market and Selayar Denai, a survey was also conducted using a questionnaire method to obtain data that would be analyzed descriptively. The results obtained were that 56 percent of traders in the Denai Lama tourist village, Pantai Labu District, had a final education of Elementary School or equivalent, with the majority of business actors being mothers aged 51 years and over as many as 44 percent, with approximately 16 types of merchandise, and There are 36 percent of traders who use banana leaves as their merchandise packaging.